2021
DOI: 10.1002/yea.3677
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol shortens the chronological lifespan of Saccharomyces cerevisiae by a pro‐oxidant mechanism

Abstract: The antioxidant phenotype caused by resveratrol has been recognized as a key piece in the health benefits exerted by this phytochemical in diseases related to aging. It has recently been proposed that a mitochondrial pro‐oxidant mechanism could be the cause of resveratrol antioxidant properties. In this regard, the hypothesis that resveratrol impedes electron transport to complex III of the electron transport chain as its main target suggests that resveratrol could increase reactive oxygen species (ROS) genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For instance, E. coli has been engineered to produce various phenolics, including resveratrol [ 116 ], a well-known antioxidant compound found in grapes and red wine. It was initially believed that resveratrol was only produced by plants, but later studies revealed that certain species of bacteria and fungi can also synthesize this compound (e.g., Saccharomyces cerevisiae ) [ 117 , 118 , 119 ]. By introducing specific genes encoding enzymes involved in phenolic biosynthesis, researchers have successfully developed bacterial strains capable of producing these compounds; Yeast production: certain strains of yeast, such as Saccharomyces cerevisiae , have been engineered to produce phenolic compounds [ 117 , 118 , 119 ].…”
Section: Microbial Natural Products Via Fermentation and Their Potent...mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, E. coli has been engineered to produce various phenolics, including resveratrol [ 116 ], a well-known antioxidant compound found in grapes and red wine. It was initially believed that resveratrol was only produced by plants, but later studies revealed that certain species of bacteria and fungi can also synthesize this compound (e.g., Saccharomyces cerevisiae ) [ 117 , 118 , 119 ]. By introducing specific genes encoding enzymes involved in phenolic biosynthesis, researchers have successfully developed bacterial strains capable of producing these compounds; Yeast production: certain strains of yeast, such as Saccharomyces cerevisiae , have been engineered to produce phenolic compounds [ 117 , 118 , 119 ].…”
Section: Microbial Natural Products Via Fermentation and Their Potent...mentioning
confidence: 99%
“…It was initially believed that resveratrol was only produced by plants, but later studies revealed that certain species of bacteria and fungi can also synthesize this compound (e.g., Saccharomyces cerevisiae ) [ 117 , 118 , 119 ]. By introducing specific genes encoding enzymes involved in phenolic biosynthesis, researchers have successfully developed bacterial strains capable of producing these compounds; Yeast production: certain strains of yeast, such as Saccharomyces cerevisiae , have been engineered to produce phenolic compounds [ 117 , 118 , 119 ]. Through genetic modifications, key enzymes involved in the phenolic biosynthetic pathway can be introduced into the yeast, enabling them to convert simple precursors into desired phenolic compounds.…”
Section: Microbial Natural Products Via Fermentation and Their Potent...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some polyphenolic compounds can cause DNA damage at high doses, even to the point of causing apoptosis [ 75 ]. Canedo-Santos et al [ 57 ] showed that the pro-oxidant properties of resveratrol accelerated the aging process and its pro-oxidant activity shortened the chronological life span of brewer’s yeast. In contrast, gallic acid, while inhibiting lipid oxidation and protein carbonyl formation, tends to promote the oxidative loss of thiol and amine groups, thereby affecting the structural properties and biological activity of proteins [ 58 ].…”
Section: Classification Properties and Beneficial Effects Of Plant Po...mentioning
confidence: 99%